Designing for diverse museum visitors’ identity exploration around inventiveness - Kaplan, Avi; Garner, Joanna K.; Rush, Amani; Smith, Monica (Frontiers in Education, 2023)
This paper describes the conceptual framework, methodology, and findings from an initial phase of research to inform the design of an exhibition at the Smithsonian National Museum of American History (NMAH) on the history of invention and innovation in sports. Organized by the Smithsonian's Lemelson Center for the Study of Invention and Innovation, the goal of the exhibition is to promote inventiveness among visitors in STEM and in life domains more broadly, with a particular emphasis on those from groups underrepresented in the NMAH visitor population and in the invention ecosystem: adolescent girls, African American youth, and people with disabilities. The research is framed by the Dynamic Systems Model of Role Identity (DSMRI)-an integrative, complex dynamic system model of identity, motivation, and actionand by a set of design principles for promoting people's agentic identity exploration. The paper describes the conceptual challenges posed by a situative identity perspective for research that aims to inform environmental design of a context that is not yet in existence and that will become relatively fixed. The paper also describes the conceptual rationale, methodology, and first phase findings from experiential sessions with participants from the target audiences, and their implications for the exhibition's design.